Immigrant Settlement Policies and Subsequent Migration - Olof Åslund (Uppsala University, Department of Economics, 2000)
Many countries consider the residential concentration among immigrants a problem. This paper studies the factors influencing individual location decisions and evaluates a Swedish attempt to change the residential distribution of refugee immigrants in the late 1980's. Despite common perceptions, I find that the evidence on increased secondary migration after the policy shift is very weak. Since people were exogenously distributed over locations, the policy provides a better way to estimate the effects of regional factors on relocation decisions. The results suggest that immigrants are attracted to regions with large populations, high representation from the own country, and large overall immigrant populations. Overall and immigrant-specific labor market opportunities affect location decisions, as does the size of the local public sector.
urn:nbn:se:uu:diva-2507
Keywords: J15; J18; J61; R23; 330; Immigration; Settlement policies; Secondary migration; Einwanderung; Niederlassungsrecht; Wirkungsanalyse; Schweden